A Ku-band coaxial relativistic transit-time oscillator with low guiding magnetic field. (28th March 2014) - Ling, Jun-Pu; He, Jun-Tao; Zhang, Jian-De; Jiang, Tao; Song, Li-Li
Abstract A novel coaxial relativistic transit-time oscillator with low guiding magnetic field is proposed and investigated to generate high power microwave at Ku-band. With the coaxial structure and a quasi body wave adopted as the operating mode, the device has a larger space-charge limiting current, higher power handling capacity, and lower guiding magnetic field. Moreover, for further improving the output power, a coaxial TM02 mode resonant reflector is well designed. Main structure parameters of the device are optimized by particle in cell simulations. A typical simulation result is that, with a 358 keV, 7.25 kA beam guided by a magnetic field of about 0.7 T, an 810 MW microwave pulse at 14.25 GHz is generated, yielding a conversion efficiency of about 31%. The primary experiments are also carried out. At a low guiding magnetic field of 0.7 T, a microwave pulse with power of 400 MW, pulse duration of 30 ns, frequency of 14.3 GHz close to the simulation one, and efficiency of 15.4% is generated.